2023
DOI: 10.3390/jof9101009
|View full text |Cite
|
Sign up to set email alerts
|

Protein Disulfide Isomerase FgEps1 Is a Secreted Virulence Factor in Fusarium graminearum

Kouhan Liu,
Xintong Wang,
Ying Li
et al.

Abstract: Protein disulfide isomerase (PDI) is a member of the thioredoxin (Trx) superfamily with important functions in cellular stability, ion uptake, and cellular differentiation. While PDI has been extensively studied in humans and animals, its role in fungi remains relatively unknown. In this study, the biological functions of FgEps1, a disulfide bond isomerase in the fungal pathogen Fusarium graminearum, were investigated. It was found that FgEps1 mutation affected nutritional growth, asexual and sexual reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In F. graminearum, the fgvelB mutant failed to produce fruiting bodies [42]. FgEps1 is a protein disulfide isomerase of F. graminearum, and it was found that ∆fgeps1 produced no perithecia on the medium [43]. The AP1 complex, a clathrin adaptor that is highly conserved, includes FgAP1σ as one of its subunits in F. graminearum.…”
Section: Genes Involves In the Formation Of Peritheciamentioning
confidence: 99%
“…In F. graminearum, the fgvelB mutant failed to produce fruiting bodies [42]. FgEps1 is a protein disulfide isomerase of F. graminearum, and it was found that ∆fgeps1 produced no perithecia on the medium [43]. The AP1 complex, a clathrin adaptor that is highly conserved, includes FgAP1σ as one of its subunits in F. graminearum.…”
Section: Genes Involves In the Formation Of Peritheciamentioning
confidence: 99%